Retinal structural changes before and after idiopathic epiretinal membrane peeling - a study using OCT segmentation - Caiado Sousa, Filipa Rebordão (2017)
Abstract Purpose: We aim to study the microstructural changes and thickness of individual retinal layers in patients with idiopathic epiretinal membrane (ERM) treated with peeling. Methods: 47 eyes of 46 patients underwent macular SD-OCT scan before and after ERM peeling. Visual acuity (VA) and central retinal layers thickness were recorded before and at the last follow up visit. Results: The layers that most have changed and contributed to the reduction of central thickness treated with peeling were the Internal Retinal Layers (IRL): Retinal Nerve Fiber Layer (RNFL), Ganglionar Cell Layer (GCL) and Internal Plexiform Layer (IPL). Conclusions: Visual acuity improvement was not statistically correlated with CMT or IRL thickness reduction, probably due to a small number of patients. However. alterations in the thickness of each retinal layers are easily obtained and its value as a noninvasive  biomarker of VA warrants further investigation. Keywords: idiopathic epiretinal membrane, individual retinal layers, thickness changes, automated segmentation, optical coherence tomography